Colon cancer and enterococcus bacteremia co-affection: A dangerous alliance - Raj Amarnani; Alwyn Rapose (Elsevier, 2017)
Adenocarcinoma of the colorectal region is one of the leading causes of cancer-related mortality in the USA and hence an important public health concern. Enterococci are emerging as an important cause of infection in the elderly. While translocation of enteric bacteria into the bloodstream is a known phenomenon in patients with infectious, inflammatory or infiltrative conditions of the bowel, a causative link between Enterococcus bacteremia and colorectal cancer has not been established in medical literature. We report the case of a patient presenting with E. faecalis bacteremia who was also diagnosed with infiltrating adenocarcinoma of the rectum. We discuss a possible relationship between these two conditions. Keywords: Enterococcus bacteremia, Colorectal adenocarcinoma